Morphophysiological responses of detached and adhered biofilms of Pseudomonas fluorescens to acidic electrolyzed water. (September 2019) - Cai, Lin-lin; Hu, Hai-jing; Lu, Qing; Wang, Hu-hu; Xu, Xing-lian; Zhou, Guang-hong; Kang, Zhuang-li; Ma, Han-jun
Abstract: Pseudomonas spp. have emerged as the main spoilage bacteria, with many strains easily forming biofilms on food-contact surfaces and causing cross-contamination. The efficacy of disinfectants against bacteria is usually tested with planktonic cells; however, the disinfection tolerance of biofilms, especially detached biofilms, remains unknown. Here, we investigated the tolerance responses of detached and adhered biofilms of Pseudomonas fluorescens to acidic electrolyzed water (AEW) by determining tolerance responses by plate counting, comparing them using a Weibull model, and verifying changes in bacterial morphology by scanning electron microscopy. The experimental data and the responses calculated using Weibull a (scale) and b (shape) parameters agreed well (R 2 values: 0.974–0.999), and we found that AEW exhibited effective antimicrobial activity against P. fluorescens, with adhered biofilms were more resistant than detached biofilms and planktonic cells. Additionally, AEW increased the bacterial membrane permeability and decreased the membrane potential, intracellular ATP concentrations, and intracellular pH while also triggering the disruption of extracellular polymeric substances. These results demonstrated that the morphophysiological responses of detached and adhered biofilms differed significantly and provided information on disinfectant-resistance strategies potentially beneficial to the development of novel disinfection approaches. Highlights: AEW exhibited effective antimicrobial activity against P. fluorescens . Adhered biofilms were more resistant to AEW treatment than detached biofilms. AEW led to different damage of cell membranes and cell homeostasis of two biofilms.